Skills for Work and the Work of Skills: Community, Labour and Technological Change in India's Artisanal Fisheries. (December 2018) - Sundar, Aparna
Artisanal cultures of work and skills transmission provide a useful point of contrast from which to think about the renewed interest in skills development as a formal, institutionalized process of training and certification for discrete and standardized skills. This article traces the transformation of practices of skill in the context of technological change in the artisanal fisheries of Kanyakumari, Tamil Nadu, to explore a set of linked questions about skills and work: How expansively or narrowly should skills be understood? What can we learn from traditional modes of skills transmission? As technology makes redundant many of the traditional skills, are we seeing a 'degradation' of work? A focus on fishing, a traditionally caste-bound occupation, also opens up questions regarding the work that skills do within a political economy, both in reproducing a given social order, and in enabling change. In tracing processes of labour recruitment in the mechanized fisheries, the article offers a further reflection, about the extent to which skills matter in securing employment, given the continued importance of networks of caste, kinship and village-based community.